1984
DOI: 10.1159/000260795
|View full text |Cite
|
Sign up to set email alerts
|

Surface Free Energy Changes of Human Enamel during Pellicle Formation

Abstract: The surface free energy and its polar- and dispersion components pertaining to pellicle-covered human enamel, sintered hydroxyapatite, Diacryl® and fluorethy-lenepropylene were determined from contact angle measurements. During the first 5 min of pellicle formation, the total surface free energy of human enamel increased from 84 to 110 erg·cm––2. After these first 5 min the surface free energy of pellicle covered solids remained constant for at least 2 h. Pellicle formation on apolar solids like flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…The results indicated that enamel shows greater variation in the contact angle values than dentin, which correspond well with previously reported data [16][17][18][19][20]. The observed variation in enamel and not in dentin must be related both to the inorganic/organic material ratio in these tissues (enamel: approx.…”
Section: Discussionsupporting
confidence: 91%
“…The results indicated that enamel shows greater variation in the contact angle values than dentin, which correspond well with previously reported data [16][17][18][19][20]. The observed variation in enamel and not in dentin must be related both to the inorganic/organic material ratio in these tissues (enamel: approx.…”
Section: Discussionsupporting
confidence: 91%
“…Salivary protein adsorption under the in vitro conditions prevailing in this study also gives rise to an increased surface free energy, although not up to the extent previously ob served by de Jong et al [1984a], This could well be due to differences in the rinsing procedures.…”
Section: Discussionmentioning
confidence: 45%
“…No information about the chemical composition of the surface is obtained, however. We have employed the technique to monitor adsorption of salivary pro teins [de Jong et al, 1984a] and fluorides [de Jong et al, 1984b;Perdok et al, 1988a] on the enamel surface.X-ray photoelectron spectroscopy (XPS), though less surface sensitive (information depth approxi mately 20-40 À), can be employed to determine the elemental composition of a surface [Andrade, 1985]. The technique is based on ejection of electrons from surface atoms by X-ray irradiation which are then dis criminated with respect to their binding energy in a specific element.…”
mentioning
confidence: 99%
“…Previous studies implicate hydrophobic interactions in the adhesion of S. sanguis (20). Both the cell and the pellicle have hydrophobic surfaces (9,27), and S. sanguis mutants exhibiting a hydrophilic phenotype are also adhesion deficient (11). Thus, hydrophobicity probably stabilizes the initial association mediated through electrostatic interactions and temper-s the marked heat capacity found in purely electrostatic adsorption systems.…”
Section: Resultsmentioning
confidence: 99%